Contemporary Use and Outcomes of Arterial Closure Devices After Percutaneous Coronary Intervention: Insights From the Veterans Affairs Clinical Assessment, Reporting, and Tracking Program. Issue 4 (18th February 2020) - Prouse, Andrew; Gunzburger, Elise; Yang, Fan; Morrison, Justin; Valle, Javier A.; Armstrong, Ehrin J.; Waldo, Stephen W.
Abstract : Background: Arterial closure devices reduce the length of bedrest after invasive cardiac procedures via the femoral approach, but there are conflicting data on their association with major bleeding and vascular complications. We thus sought to evaluate the contemporary use of femoral arterial closure devices and their association with major bleeding among patients undergoing percutaneous coronary intervention. Methods and Results: We identified patients undergoing percutaneous intervention via the femoral approach within the Veterans Affairs Healthcare System from December 2004 through September 2018. The association between arterial closure device use and major bleeding was evaluated using both propensity matching and instrumental variable analyses, incorporating contrast‐induced nephropathy as a falsification end point. We identified 132 373 percutaneous coronary interventions performed by 681 operators, with closure device use increasing 1.2% each year (linear trend P <0.001). In a propensity‐matched cohort, closure devices were associated with a 1.1% reduction in periprocedural bleeding (95% CI, −1.5% to −0.6%). Closure devices were also associated with a numerical decrease in contrast‐inducted nephropathy that did not reach statistical significance (−0.6%; 95% CI, −1.3% to 0.1%). In an instrumental variable analysis of closure device use, there was no difference in the bleeding rate between those who received a closure device and those who did not (0.2%; 95% CI, −0.9% to 1.2%). Conclusions: Arterial closure devices are associated with a reduction in major bleeding within a propensity‐matched cohort. This association dissipates in an instrumental variable analysis, highlighting some of the methodologic limitations of comparative effectiveness research in observational analyses.